Estimating the influence of disruption on highway networks using GPS data. (January 2022) - Yang, Zhenzhen; Liu, Feng; Gao, Ziyou; Sun, Huijun; Zhao, Jiandong; Janssens, Davy; Wets, Geert
Highlights: The method is based on the Bayesian theory and thrice-standard-error principle. The method can better account for the data fluctuation and deduce the results. Disrupted roads, detour roads, and congestion roads can be accurately determined. GPS data make the estimation of disruption more quickly and the coverage wider. Abstract: Incidents, such as natural disasters, public events, and holidays, often cause problems to highways, even paralyze the operation of the whole networks, leading to a serious threat to travel efficiency and safety of the public. To provide better transport management and plans for emergencies, it is important to quickly and accurately identify such incidents and estimate their disruptive effects on the networks. To this end, a novel approach has been proposed in this paper, which is based on the Bayesian theory and thrice-standard-error principle while utilizing vehicle GPS data. Two important indicators, including traffic flows and congestion indexes, along with their change ratios, are built to detect the incidents and evaluate the extent of the disruption. The specific disrupted and detour roads are further determined. The proposed method has been tested using two real-world events in China, and the potential and effectiveness of this technique are demonstrated. With more and more vehicles being equipped with GPS devices worldwide, the designed method can be easily transferable to other countries, paving a way for the adoption of the approach for a more spatial–temporal sensitive highway network disruption analysis method that supports the establishment of a more resilient transport system for emergencies.